The Influence of Express Microfinance in Improving the Welfare of Market Traders (Case Study of Bank Mitra Mentari Sejahtera Ponorogo) - Robingatus Sa’diyah; Aprillia Rachmawaty; Muhammad Candra Setiawan (Journal of Sharia Economic Law, 2025)
Usury-based financing practices through loan sharks or thithil banks are still common among traditional market traders. This situation prompted PT. BPRS Mitra Mentari Sejahtera Ponorogo to launch the Micro Express Financing (ME) product in May 2019 as a sharia-based financing alternative. This study aims to analyze the background, mechanisms, financing contracts, and impact of Micro Express Financing on market traders. This study was field research using a descriptive qualitative approach. Data were obtained through interviews with the bank, specifically Micro Field Officers (PLM), Micro Express financing customers, as well as observation and documentation. The results indicate that Micro Express Financing uses a murabahah contract, which aligns with the business characteristics of market traders. Simple procedures, fast disbursement, no collateral, and a proactive service system are key factors in attracting customers. This financing has positive impacts in terms of increased liquidity, business development, and helping market traders gradually move away from usury practices. However, challenges include irregular installment payments and low customer financial literacy.